Crossing thresholds : feminist essays in social history - Kosambi, Meera (Ranikhet : Permanent Black ; New Delhi : Distributed by Orient Longman, 2007)
Articles chiefly with reference to Maharashtra, India.
Includes bibliographical references (p. [369]-390) and index.
Keywords: Feminism -- India -- Maharashtra -- History; Women -- India -- Maharashtra -- Social conditions -- 20th century